The efficacy of incorporating partial squats in maximal strength training - Bazyler, C. D.; Sato, K.; Wassinger, C. A.; Lamont, H. S.; Stone, M. H. (The Journal of Strength and Conditioning Research, 2014)
The purpose of our study was to examine the effects of 2 different training methods on dynamic and isometric measures of maximal strength. Seventeen recreationally trained men (1 repetition maximum [1RM] squat: 146.9 ± 22.4 kg) were assigned to 2 groups: full range of motion (ROM) squat (F) and full ROM with partial ROM squat (FP) for the 7-week training intervention. Repeated measures analysis of variance revealed that there was a statistically significant group-by-time interaction for impulse scaled at 50, 90, and 250 milliseconds at 90° of knee flexion and rate of force development at 200 milliseconds with 120° of knee flexion (p < 0.05). There was also a statistically significant time effect (p < 0.05) for the 1RM squat, 1RM partial squat, isometric squat peak force allometrically scaled (IPFa) 90°, IPFa 120°, and impulse allometrically scaled at 50, 90, 200, and 250 milliseconds at 90° and 120° of knee flexion. Additionally, the FP group achieved statistically larger relative training intensities (%1RM) during the final 3 weeks of training (p < 0.05). There was a trend for FP to improve over F in 1RM squat (+3.1%, d = 0.53 vs. 0.32), 1RM partial squat (+4.7%, d = 0.95 vs. 0.69), IPFa 120° (+5.7%, d = 0.52 vs. 0.12), and impulse scaled at 50, 90, 200, and 250 milliseconds at 90° (+6.3 to 13.2%, d = 0.50-1.01 vs. 0.30-0.57) and 120° (+3.4 to 16.8%, d = 0.45-1.11 vs. 0.08-0.37). These larger effect sizes in the FP group can likely be explained their ability to train at larger relative training intensities during the final 3 weeks of training resulting in superior training adaptations. Our findings suggest that partial ROM squats in conjunction with full ROM squats may be an effective training method for improving maximal strength and early force-time curve characteristics in men with previous strength training experience. Practically, partial squats may be beneficial for strength and power athletes during a strength-speed mesocycle while peaking for competition.